MEK inhibitors block growth of lung tumours with mutations in ataxia-telangiectasia mutated - Smida, Michal; Fece de la Cruz, Ferran; Kerzendorfer, Claudia; Uras, Iris Z; Mair, Barbara; Mazouzi, Abdelghani; Suchankova, Tereza; Konopka, Tomasz; Katz, Amanda M; Paz, Keren; Nagy-Bojarszky, Katalin; Muellner, Markus K; et al. (Nature communications, 2016)
Lung cancer is the leading cause of cancer deaths, and effective treatments are urgently needed. Loss-of-function mutations in the DNA damage response kinase ATM are common in lung adenocarcinoma but directly targeting these with drugs remains challenging. Here we report that ATM loss-of-function is synthetic lethal with drugs inhibiting the central growth factor kinases MEK1/2, including the FDA-approved drug trametinib. Lung cancer cells resistant to MEK inhibition become highly sensitive upon loss of ATM both in vitro and in vivo. Mechanistically, ATM mediates crosstalk between the prosurvival MEK/ERK and AKT/mTOR pathways. ATM loss also enhances the sensitivity of KRAS- or BRAF-mutant lung cancer cells to MEK inhibition. Thus, ATM mutational status in lung cancer is a mechanistic biomarker for MEK inhibitor response, which may improve patient stratification and extend the applicability of these drugs beyond RAS and BRAF mutant tumours.
Keywords: nádory plic; Lung Neoplasms; myši nahé; Humans; inhibitory proteinkinas; Benzamides; Proto-Oncogene Proteins B-raf; Pyrimidinones; Urea; Thiophenes; Pyridones; mutace; ras Proteins; difenylamin; pyrimidinony; ATM protein; lidé; Mice, Nude; zvířata; proliferace buněk; xenogenní modely - testy protinádorové aktivity; močovina; Diphenylamine; protoonkogenní proteiny B-Raf; Protein Kinase Inhibitors; Cell Proliferation; Ataxia Telangiectasia Mutated Proteins; RNA Interference; nádorové buněčné linie; pyridony; benzamidy; Ras proteiny; Xenograft Model Antitumor Assays; Animals; Cell Line, Tumor; thiofeny; Mutation; RNA interference